Application of retinal nerves fiber layer examination – GDx in patients with multiple sclerosis - Jankowska-Lech, Irmina; Terelak-Borys, Barbara; Grabska-Liberek, Iwona; Wasyluk, Jaromir; Palasik, Witold (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The purpose of our study is to evaluate retinal fiber layer thickness with scanning polarymetry laser (GDx), in patients suffering from SM with or without optic nerve symptoms. Multiple sclerosis proceeds to neurodegenerative changes and commonly appears with retrobulbar optic nerve damage. Examination of retinal nerves fiber layer examination with scanning laser polarymetry (GDx) enables to perform quantitative evaluation of retinal nerves fiber layer thickness within the area around the optic nerve disc. It finds application in diagnosis and monitoring of glaucoma, however its usefulness as a tool evaluating optic nerve in multiple sclerosis, has not been proved yet. Materials and methods: Subjects diagnosed with multiple sclerosis (SM) were divided into 2 groups. First group was comprised of subjects, who suffered from at least one episode of retrobulbar neuritis, in at least one eye. Second group was made up of 8 subjects with no history of retrobulbar neuritis. Retinal nerves fiber layer thickness was measured with scanning polarymetry laser (GDx). Results: Symptoms of retinal nerves fiber layer damage, were discovered with GDx significantly more common in first group (70% vs 18.75% accordingly). Conclusions: Moreover, we stated that evaluation with scanning polarymetry laser might be precious method in discovering retinal nerves fiber layer damage in the course of multiple sclerosis. Presence of defects in retinal nerves fiber layer in patients suffering from multiple sclerosis with no history of retrobulbar neuritis may suggest subclinical damage of optic nerve.